2011
DOI: 10.4067/s0301-732x2011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Aplicación del bioensayo EROD-H4IIE para la determinación de dioxinas en carnes de pollos broiler: un estudio de equivalencia con la cromatografía de gases de alta resolución acoplada a espectrometría de masas de alta resolución

Abstract: ARTÍCULO ORIGINALAplicación del bioensayo EROD-H4IIE para la determinación de dioxinas en carnes de pollos broiler: un estudio de equivalencia con la cromatografía de gases de alta resolución acoplada a espectrometría de masas de alta resolución # � Application of the EROD-H4IIE bioassay for the determination of dioxins in broiler chicken meat: an equivalence study with high resolution gas chromatography coupled to high resolution mass spectrometry SUMMARYThe EROD bioassay with H4IIE cell line was applied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These samples were analysed by HRGC/HRMS, effectively confirming 36 as positive. Overestimates have also been reported in the analysis of poultry samples (Schoffer et al 2011) and ash (Till et al 1997). The difference between the two methods may be due to compounds that can trigger the aryl hydrocarbon receptor (AhR) pathway, such as polycyclic aromatic hydrocarbons (Chaloupka et al 1993), polybrominated compounds (Baston and Denison 2011), indol-3-carbinol (13C), which is present in cruciferous plants and has been described as a moderate activity binder with the AhR receptor (Chen et al 1996), in addition to DL-PCBs which in this study work were not analysed by HRGC/HRMS.…”
Section: Comparison Of Hrgc/hrms and H4iie-erod Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These samples were analysed by HRGC/HRMS, effectively confirming 36 as positive. Overestimates have also been reported in the analysis of poultry samples (Schoffer et al 2011) and ash (Till et al 1997). The difference between the two methods may be due to compounds that can trigger the aryl hydrocarbon receptor (AhR) pathway, such as polycyclic aromatic hydrocarbons (Chaloupka et al 1993), polybrominated compounds (Baston and Denison 2011), indol-3-carbinol (13C), which is present in cruciferous plants and has been described as a moderate activity binder with the AhR receptor (Chen et al 1996), in addition to DL-PCBs which in this study work were not analysed by HRGC/HRMS.…”
Section: Comparison Of Hrgc/hrms and H4iie-erod Resultsmentioning
confidence: 99%
“…In this study the bioassay lasted an average of 12 days from the beginning of the extraction until the reporting of the results and it showed a high sensitivity (LOD = 0.142 ± 0.1208) and a high reproducibility considering the quality control criteria of the assay. Schoffer et al (2011) demonstrated the equivalence between the bioassay and HRCG/HRMS for the detection of dioxins in broiler chicken meat, reporting that it can be a useful technique to biomonitor these xenobiotics in animal production. However, in this study it was not possible to estimate a significant equivalence between the results obtained from both methods in pork samples, because there was not significant correlation between the data produced by the two analytical methods, this precluded the use of a model to estimate the expected value of PCDD/Fs contamination, which would be obtained by HRCG/HRMS, only if the EROD-H4IIE bioassay is used.…”
Section: Comparison Of Hrgc/hrms and H4iie-erod Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These chemical analyzes require pretreatment to preserve the sample during transfer to the laboratory, to avoid altering the results. This occurs, for example, in gas chromatography and mass detection analyzes; expensive and large equipment that requires its use in the laboratory (Schoffer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The modified protocol of Tillitt et al (1991) was used, as described by Schoffer et al (2011) and Samsing et al (2011), and incorporated into the standard procedure of the CIE Mayor P-TEC-001. The results of the analysis were expressed in pg TCDD-EQ/g of sample.…”
Section: Elaboration Of Databasesmentioning
confidence: 99%